(untitled) (Biological Sciences - PJSIR, 2022)
Analytical procedures have been developed for extraction, cleanup, identification and quantification of multiple residues of organochlorine, organophosphorus and synthetic pyrethroid pesticides in cotton seeds, collected fromcotton growing areas of Punjab and Sindh provinces of Pakistan. These methods are efficient and reliable and allowed lipid removal to a large extent.